Development of K-Workers Employability Skills Measurements Indicators in Agricultural Sector in Malaysia - Che Rus, Ridzwan; Mamat, Abu Bakar; Hasnan, Khairul Anuar; Hanapi, Zaliza; Mat Nashir, Irdayanti (Journal of Technical Education and Training, 2019)
Issue of skilled and knowledge worker is an issue that frequently discussed among agricultural training institutions and employers in the sector. It is viewed seriously by Malaysian government through Agrofood Policy 2011-2015 by emphasizing agricultural workers that are highly skilled and knowledgeable to assist Malaysia achieves high-income developed nation status. However, what are the characteristics of those high skilled and knowledge workers? This question is the base of this research. By using qualitative approach, modified Delphi technique / method is chosen as the research framework. Eleven experts from various stakeholders such as agriculture lecturer, leaders of agricultural training institutions, agricultural instructor and agricultural industry employer in Malaysia. Finding reveals ten characteristics of k-workers that are needed to enable them to have high employability skill in order to satisfy / fulfil national requirement of skilled workforce. This finding can be used as a measurement basis for employability skill level of labour market in agricultural sector in Malaysia.